What is Being Said About Internal Marketing? A Study of the Brazilian Business Administration Academic Production - Fernanda Roda de Souza Araújo Cassundé; Nildo Ferreira Cassundé Junior; Salomão Alencar de Farias; José Ricardo Costa de Mendonça (BBR: Brazilian Business Review)
This study had the purpose of identifying how internal marketing is being addressed in the Brazilian production in the field of Administration. To this end, the major periodicals in the field and the database of the National Association of Graduate Programs in Business Administration (Anpad) and Scientific Periodicals Electronic Library (SPELL) were investigated under the guidance of research propositions found in Farias (2010). After a search of the entire historical database of publications adopted as corpus, only 13 articles were discovered and retrieved from the period 1961-2012.The findings of this study show that the state of knowledge about internal marketing in Administration is quite specific and, in some cases, surprisingly nonexistent. This aspect allows us to notice various concerns, among which the most significant one is: for what reason has internal marketing not been receiving - at least with respect to periodic and national Administration congresses - the attention it deserves? It is expected to contribute to the understanding of how scholars are studying the internal marketing of the area in the Brazilian context.